Kreativitas Guru PPKn dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan - Latif, Abdul; Susiatik, Titik; Srihadi, Srihadi (Journal of Democratia; Vol 2 No 1 (2024): Jurnal Democratia : Pendidikan Pancasila dan Kewarganegaraan, Moral, Karakter, dan Hukum, 2024)
describe teacher creativity in increasing student learning motivation in Civics subjects at Al-Qur'an and Da'wah Alam Secang Vocational Schools. This research was conducted at Al-Qur'an and Da'wah Alam Secang Vocational Schools. The type of research used is qualitative research using a descriptive approach. The population consisted of all Civics teachers at Al-Qur'an and Da'wah Alam Secang Vocational Schools. The sampling method in this study was using a random sampling technique. So, the sample in this study were 2 Civics teachers for class X and class XI at SMK Al-Qur'an and Da'wah Alam Secang. The data was collected through observation, interviews, and documentation, by interviewing 2 Civics teachers, namely the Class X Civics teacher and the Class XI Civics teacher as respondents. The data analysis techniques used are: (1) data reduction; (2) data presentation; (3) drawing conclusions. The results of the study show that a) the development of teacher teaching creativity to foster students' interest in learning and teachers are expected to create a teaching strategy that is quite effective and creative, b) creativity in designing lesson plans to plan learning and carry out learning in accordance with educational goals, c) creativity in managing teaching and learning programs the teacher must really know the situation and condition of the students before providing material in class, d) creativity in class management, namely students respond to the material that the teacher conveys during the learning process, e) creativity in using learning methods and media so that learning class can attract students' attention. The factors that influence students' learning motivation in Civics subjects are: (1) internal factors such as desire or curiosity that encourage students to continue learning inside and outside of school; (2) external factors such as teachers, schools, friends, environment, family/parents. External factors that make students at Al-Qur'an and Da'wah Alam Secang Vocational Schools less motivated in learning are: a) lack of support from family/parents; b) the environment around students such as the influence of peers who like not to study, and are lazy to follow Civics subjects